Co-existence of people and orangutan in Sumatra. Stabilising gradients for landscape multifunctionality - Tata HL; Widayati, A.; Mulyoutami E; Noordwijk, Meine van (World Agroforestry Centre, 2011)
Multifunctional landscapes and species-rich agroforests can support biodiversity conservation. Command- and-control conservation approaches tend to create sharp distinctions between protected areas and surrounding agriculture. Can a village agroforest forest landscape gradient be stable? Or is it part of a continuous process of forest conversion that in the end will leave hardly any conservation values intact? The landscape of Batang Toru, Sumatra offers a case study. It is home to a genetically unique Sumatran orangutan population and to people of diverse backgrounds. It provides insight into the types of government policy and market-based instruments that are needed to stabilise the existing gradient.